A Versatile Li6.5In0.25P0.75S5I Sulfide Electrolyte Triggered by Ultimate‐Energy Mechanical Alloying for All‐Solid‐State Lithium Metal Batteries. Issue 36 (4th August 2021) - Jiang, Zhao; Peng, Hongling; Liu, Yu; Li, Zhongxu; Zhong, Yu; Wang, Xiuli; Xia, Xinhui; Gu, Changdong; Tu, Jiangping
Abstract: Sulfide solid electrolytes (SSEs) have captured plentiful interest on account of their high ionic conductivity and appropriate mechanical strength. However, the poor air stability and cost‐intensive preparation process of SSEs limit their applications. Herein, a novel ultimate‐energy mechanical alloying (UEMA) approach is applied to rapidly synthesize the argyrodite‐type electrolytes in a one‐pot process. According to the hard‐soft‐acid‐base theory and the first‐principles density functional theory (DFT) calculation, In‐doping in Li6 PS5 I is attempted to enhance air stability and the experimental results demonstrate the success of this approach. The synthesized Li6.5 In0.25 P0.75 S5 I electrolyte has a high ionic conductivity (1.06 mS cm –1 ), and also presents excellent interfacial stability against Li metal, benefiting from the formation of a LiI‐rich interphase layer. The assembled Li–S battery with Li6.5 In0.25 P0.75 S5 I as an interlayer delivers a high discharge capacity (954 mAh g –1 ) and presents the capacity retention of 96% after 200 cycles. The In‐doped Li6 PS5 I is a novel promising electrolyte with high air stability and ionic conductivity for the application of all‐solid‐state lithium metal batteries. Abstract : Herein, the ultimate‐energy mechanical alloying method is adopted to rapidly synthesize argyrodite‐type electrolytes in a one‐pot process. In‐doping is further utilized to optimize the Li6 PS5 I electrolyte. The Li6.5 In0.25 P0.75 S5 I electrolyte with high ionic conductivity, good air stability, and excellent interfacial stability is obtained and leads to a high discharge capacity (954 mAh g –1 ) and a capacity retention of 96% after 200 cycles.